A single viral amino acid shapes the root system architecture of a plant host upon virus infection - Roy, Brandon G.; Fuchs, Marc (BMC microbiology, 2024)
Background Grapevine fanleaf virus (GFLV) is one of the most detrimental viral pathogens of grapevines worldwide but no information is available on its effect on the root system architecture (RSA) of plant hosts. We used two wildtype GFLV strains and their single amino acid mutants to assess RSA traits in infected Nicotiana benthamiana and evaluate transcriptomic changes in host root gene expression in replicated time course 3’RNA-Seq experiments. Mutations targeted the multi-functional GFLV-encoded protein 1E Pol*/Sd , a putative RNA-dependent RNA polymerase and determinant of foliar symptoms in N. benthamiana plants. Results Plant infection with wildtype GFLV strain GHu and mutant GFLV strain F13 1E Pol G802K , both carrying a lysine in position 802 of protein 1E Pol*/Sd , resulted in a significantly lower number of root tips (-30%), and a significantly increased average root diameter (+ 20%) at 17 days post inoculation (dpi) in comparison with roots of mock inoculated plants. In contrast, the RSA of plants infected with wildtype GFLV strain F13 and mutant GFLV strain GHu 1E Pol K802G , both carrying a glycine in position 802 of protein 1E Pol*/Sd , resembled that of mock inoculated plants. Modifications of RSA traits were not associated with GFLV titer. Root tissue transcriptome analysis at 17 dpi indicated dysregulation of pattern recognition receptors, plant hormones, RNA silencing, and genes related to the production of reactive oxygen species (ROS). For wildtype GFLV strain GHu, RSA modifications were correlated with an abundant accumulation of ROS in the pericycle of primary roots at 7 dpi and the duration of vein clearing symptom expression in apical leaves. Dysegulation of a hypersensitive response was an overarching gene ontology found through enrichment analyses of 3’RNA-Seq data. Conclusions Our findings revealed the causative role of lysine in position 802 of protein 1E Pol*/Sd in a novel RSA phenotype during viral infection and documented GFLV- N. benthamiana interactions at the root level based on (i) antiviral response, (ii) receptor mediated production of ROS, and (iii) hormone regulation. A correlation between above and below ground symptoms was reported for the first time in plants infected with wildtype GFLV strain GHu. Further work is warranted to test whether the modified RSA of a plant host might impact GFLV acquisition and transmission by the ectoparasitic dagger nematode Xiphinema index .